ANALYSIS OF FACTORS AFFECTING DECISION OF FIXED ASSETS INVESTMENT IN BASIC AND CHEMICAL MANUFACTURING COMPANIES - Phiter Louis Gunawan; Christine Gunawan; Yois Nelsari Malau (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The purpose of this study is to examine and analyze the factors that influence fixed asset investment decisions in basic and chemical manufacturing companies on the Indonesia Stock Exchange (IDX) for the 2017-2019 period, where the independent variables used are current ratio, operational cash flow, return on assets and age of the company and investment decisions on fixed assets as the dependent variable. This study used purposive sampling to obtain 22 sample companies from 74 population companies listed on the IDX for the period 2017-2019 (3 years). Simultaneous research results with the F test show that the current ratio, operating cash flow, return on assets, and company age together have a positive effect on fixed-asset investment decisions. The results of the research partially with the T-test showed that the current ratio and operating cash flow variables partially had no significant effect on fixed-asset investment decisions, while return on assets and company age had a partial and significant effect on fixed-asset investment decisions with the coefficient determination of 21.10%. Keywords: Company Age, Current Ratio, Fixed Asset Investment Decisions, Operational Cash Flow, Return On Assets